1992
DOI: 10.2527/1992.70102970x
|View full text |Cite
|
Sign up to set email alerts
|

Performance and health of weanling bulls after butorphanol and xylazine administration at castration

Abstract: A total of 268 crossbred, 6- to 9-mo-old, bull calves (214 +/- 19 kg) were used in two separate 27-d experiments to assess the effects of butorphanol and xylazine administration (BXA) on the subsequent performance and health of beef calves. In each experiment, calves were randomly allotted to four treatment groups: 1) castration with BXA, 2) castration without BXA, 3) no castration with BXA, and 4) no castration without BXA. There were two replicates within each experiment. The intravenous administration of .0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 5 publications
0
37
1
Order By: Relevance
“…Previous reports showed an increase in these two acute-phase proteins (APP) at an earlier time (days 1, 3, and 7 post-castration) in younger animals (Faulkner et al, 1992;Fisher et al, 1997;Earley and Crowe, 2002;Ting et al, 2003;Pang et al, 2006). Horadagoda et al (1999) reported that APP, such as serum amyloid-A and haptoglobin are excellent markers for indicating acute inflammatory conditions in cattle.…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports showed an increase in these two acute-phase proteins (APP) at an earlier time (days 1, 3, and 7 post-castration) in younger animals (Faulkner et al, 1992;Fisher et al, 1997;Earley and Crowe, 2002;Ting et al, 2003;Pang et al, 2006). Horadagoda et al (1999) reported that APP, such as serum amyloid-A and haptoglobin are excellent markers for indicating acute inflammatory conditions in cattle.…”
Section: Discussionmentioning
confidence: 98%
“…Castration of bull calves intended for beef production is a commonly performed management practice in livestock operations in the United States, accounting for approximately 16 million procedures per yr (USDA, 2015). Bull calves are routinely castrated at livestock operations to decrease secondary sex characteristics, minimize aggressive behavior, facilitate management, and improve beef quality (Faulkner et al, 1992;Rust et al, 2007;Gonzalez et al, 2010). At least 77% of all bull calves were castrated on almost 60% of all cow-calf operations in the United States during 2007 (USDA, 2008a).…”
Section: Production Practicesmentioning
confidence: 99%
“…In cattle, increased serum or plasma haptoglobin concentration was found after experimentally induced inflammation [22,28], trauma [35,47,52] and also after experimental [65] and natural inflammatory diseases [6,104] (Tab. IV).…”
Section: Bovine Haptoglobinmentioning
confidence: 99%
“…Banding is not associated with changes in the Hp concentration [41], whereas castration is followed by an increased Hp level Cattle Experimental local aseptic inflammation [22,28] Infection with bovine virus diarrhea virus and Pasteurella haemolytica [61] Experimental infection with P. multocida [33] Experimental infection with P. haemolytica [87] Infection with bovine herpes virus 1 and P. haemolytica A1 [58] Experimental infection with bovine respiratory syncytial virus [65] Natural infections with foot-and-mouth disease virus [81] Mastitis [40,68,70,130,152] Various acute infections under field conditions [164] Clinical respiratory tract disease [188] Various inflammatory diseases [6] Acute inflammations [104] Castration [35,47,50,51,52] Ruminotomy [119] Metritis [71,165,166] Severe uterine bacterial post partum contamination [160] Fatty liver (hepatic lipidosis) [87,124,192] Nonfeeding for 3 days [88] Starvation for 2 days combined with Dexamethasone treatments [193] Transportation for 2 days [120] Major injuries at slaughter/culling [69,149] Horse Experimental aseptic arthritis [80] Experimental local aseptic inflammation [113,171] Experimentally induced noninfectious ...…”
Section: Bovine Haptoglobinmentioning
confidence: 99%